Six Sigma-DMAIC (Define, Measure, Analyze, Improve, And Control) Analysis in Reducing Building Structural Defects (Case Study: Emirates Indonesia Cardiology Hospital Project) - Mustika, Risti; Suwandi, Putri Anggi Permata; Kristiawan, Agung (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2025)
Abstract. Construction projects often face challenges in maintaining quality, one of which is structural defects that can affect the quality and safety of the building. This study aims to analyze the level of defects in column, beam, and slab structures using the Six Sigma DMAIC method and provide solutions to improve these defects. The study was conducted on the Emirates Indonesia Cardiology Hospital Building Construction Project in Surakarta. The method used is a quantitative descriptive approach with the stages of Define, Measure, Analyze, Improve, and Control. Data were obtained through field observations, interviews, documentation, and secondary project data. The analysis results show that the average sigma level value is above 3, with the highest level in the column structure reaching 4.3 sigma for the type of concrete flow defect. The main causes of defects come from human factors, work methods, materials, and supervision. Improvement solutions are formulated using a fishbone diagram analysis approach and the assistance of NVIVO software for qualitative data analysis. This study shows that the Six Sigma DMAIC method is effective in identifying and reducing defects in concrete structure work and can be used as a quality control strategy in construction projects.Keywords: Six Sigma, DMAIC, Structural Defects, Construction Quality, NVIVO